Novel technique to accurately measure femoral diameter using a Thomas splint. Issue 11 (November 2017) - Liew, Ignatius; Qureshi, Mobeen; Joseph, Jibu; Bailey, Oliver
Abstract: Introduction: During surgical management of femoral shaft fractures, difficulties arise when treating patients with narrow femoral diaphyseal canals, such as young patients and those with dysplastic femurs secondary to underlying pathology. Accurate pre-operative assessment of the femoral diaphyseal canal diameter would allow the surgeon to plan surgical technique and ensure appropriate equipment was available, such as narrow, unreamed or paediatric sized nails. Technique: When secured to the patient both longitudinal rods of the main Thomas Splint component lie parallel with the femoral shaft and horizontal to the radiographic x-ray plate. The diameter of these rods are 13 mm (Adult and paediatric). Using the calibration tool, we calibrate the diameter of the Thomas Splint to 13 mm, accurately measuring any further detail on that radiograph, such as the diaphyseal canal diameter. Conclusion: Accurate knowledge pre-operatively of radiographic measurements is highly valuable to the operating surgeon. This technique can accurately measure femoral canal diameter using the Thomas splint, negates the requirement for a calibration marker, is reproducible, easy to perform, and is indispensible when faced with a patient with a narrow femoral canal in a diaphyseal femoral fracture. (181 words)